Effects of a magnetic field on circulation in an advanced inclined isothermal sectional surface with mass and heat transfer - Sundar Raj, M.; Nagarajan, Gnanavel; Rajaraman, Rengasamy; Saravanan, Balasubramani; Muthucumaraswamy, Rajamanickam (Zielona Góra: Uniwersytet Zielonogórski)
The study includes a Nusselt number table for various parameters corresponding to an increase in the Prandtl number, as well as the Sherwood number for different components as the Schmidt number escalates. This work helps us learn more about the complicated interactions between magnetic fields and fluid movement, which is useful for many engineering and science projects.
Keywords: accelerated vertical plate; heat and mass transfer; isothermal; inclined plate; mass diffusion